PENGARUH PENGGUNAAN SISTEM KOMERSIAL ELEKTRONIK, LAW ENFORCEMENT, DAN SELF ASSESSMENT SYSTEM TERHADAP PENGHINDARAN PAJAK - Alya Nur Afifah (2023)
The purpose of this study is to determine the effect of the use of electronic commercial systems, law enforcement, and self-assessment systems on tax evasion. This research is a quantitative study with a population of business people through e-commerce in Bogor City. The sample in this study was obtained through the snowball sampling method, amounting to 93 respondents. The analytical method used is multiple linear regression analysis with the help of SPSS 25 software. The results show that the self-assessment system has a significant effect on tax evasion, while the use of electronic commercial systems and law enforcement does not have a significant effect on tax evasion.